Multimedia physics practicum reflective material based on problem solving for science process skills - Wawan Kurniawan; Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; M Hidayat; Nugroho Kurniawan; Linda Zaenati Nur Farida (Institute of Advanced Engineering and Science, 2019)
Purpose: This study aims to determine the differences in science process skills in each class in the Physics Education Study Program. Methodology: This research is a quantitative study with a comparison design. The research sample used amounted to 108 students with details of 54 control class students who used conventional guidebooks, while the control class totaling 54 students used a science process skill guide. The research data was obtained from observation activities using observation sheets of science process skills which were analyzed using descriptive statistics and inferential statistics. Finding: The results showed that there were significant differences in the mastery of science process skills of students seen from the value of the average mastery of science process skills of students using guidebooks based on science process skills. The experimental class has an average science process skill that is better than the control class.